2015
DOI: 10.1039/c4dt03878a
|View full text |Cite
|
Sign up to set email alerts
|

New NIR-emissive tetranuclear Er(iii) complexes with 4-hydroxo-2,1,3-benzothiadiazolate and dibenzoylmethanide ligands: synthesis and characterization

Abstract: New tetranuclear heteroleptic complexes [Er4(dbm)6(O-btd)4(OH)2] (1) and [Er4(dbm)4(O-btd)6(OH)2] (2) (O-btd = 4-hydroxo-2,1,3-benzothiadiazolate and dbm = dibenzoylmethanide) and their solvates with toluene, THF and CH2Cl2 were prepared using two synthetic approaches. The structures of the products were confirmed by single-crystal X-ray diffraction. Magnetic properties of 1 and 2 are in good agreement with X-ray data. The effective magnetic moment (μeff) values at 300 K for 1 and 2 corresponds to a system of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 46 publications
(66 reference statements)
0
14
0
Order By: Relevance
“…An analysis of the correlation between CB ave distance and the associated angles q, f,a nd F for each structure shows that those with close contacts (CB ave van der Waals radii sum N + S = 3.35 ) [78] have angular ranges of q ave = 67.7-89.78 (mean 74.08), f ave = 0-36.38 (mean 1.78)a nd F ave = 149.6-179.58 (mean 171.68). Every structure in this category contains ah ighly aligned square planar interaction, with angles approaching f% 08, q % 908,a nd F % 1808.T he shortest (2.89 ), [76] middle (3.39 ) [79] and longest (3.95 ) [77] CB ave distances,r espectively,i llustrate the marked diversity in 2S-2N square 2,1,3-benzothiadiazole dimer structures that fall within the 2.89-4.0 CB ave range ( Figure S10). The strikingly high prevalence of diverse structures (39) containing both sub-van der Waals S···Nc ontacts and highly aligneds quare planar interactions suggestst hat the square attraction out-competes the myriad of other substituent interactions during packing.…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of the correlation between CB ave distance and the associated angles q, f,a nd F for each structure shows that those with close contacts (CB ave van der Waals radii sum N + S = 3.35 ) [78] have angular ranges of q ave = 67.7-89.78 (mean 74.08), f ave = 0-36.38 (mean 1.78)a nd F ave = 149.6-179.58 (mean 171.68). Every structure in this category contains ah ighly aligned square planar interaction, with angles approaching f% 08, q % 908,a nd F % 1808.T he shortest (2.89 ), [76] middle (3.39 ) [79] and longest (3.95 ) [77] CB ave distances,r espectively,i llustrate the marked diversity in 2S-2N square 2,1,3-benzothiadiazole dimer structures that fall within the 2.89-4.0 CB ave range ( Figure S10). The strikingly high prevalence of diverse structures (39) containing both sub-van der Waals S···Nc ontacts and highly aligneds quare planar interactions suggestst hat the square attraction out-competes the myriad of other substituent interactions during packing.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have established the synthesis of pentanuclear lanthanide hydroxo clusters by treatment of the trichlorides of the smaller lanthanides [LnCl 3 ·(H 2 O) n ] (n = 6, 7) with dibenzoylmethane (Ph 2 acacH) in organic solvents in the presence of an organic base such as triethylamine or KOtBu. Another route to these compounds is by treatment of [Ln(Ph 2 acac) 3 10 ] (Ln = Y, [10] Nd, [49] Eu, [50][51][52][53] Tb, [52] Dy, [54] Ho, [53] Er, [49,55] Yb; [49] Scheme 3), in which the lanthanide atoms build up a square pyramidal scaffold by occupying its vertices (Figure 6), were obtained. In each of these structures, the square base face of the pyramid is capped by one μ 4 -oxygen atom, whereas its four triangular faces are capped by one μ 3 -oxygen moiety each.…”
Section: Towards a Rational Synthesis Of Pentanuclear Clustersmentioning
confidence: 99%
“…[34] In a similar way the tetranuclear complexes [Er 4 (Ph 2 acac) 6 -(O-btd) 4 4 (O-btd) 6 (OH) 2 ] (O-btd = 4-hydroxy-2,1,3-benzothiadiazolate) were synthesized. [55] Obviously, the choice of the right co-ligand is crucial for obtaining the pentanuclear structural motif. We showed that amino acids are the ideal co-ligands to stabilize the pentanuclear lanthanide scaffold.…”
Section: Functionalized Pentanuclear Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, 2,1,3-benzothia/selenadiazoles found numerous applications as electron-acceptor or/and luminescent building blocks of real or potential molecular functional materials for electronics, optoelectronics and photovoltaics. 4,5,[13][14][15][16][17][18][19][20][21][22][23][24][25] Despite fluorinated (hetero) aromatics are promising for electronic and optoelectronic applications, 26,27 fluorinated 2,1,3-benzothia/selenadiazoles are less studied in this context. Hydrogen replacement by fluorine affects many properties of (hetero) aromatics including (hetero) aromaticity itself.…”
Section: Introductionmentioning
confidence: 99%